Study title: A systematic review of RCTs to examine the risk of adverse cardiovascular events with nicotine use - Kim, Mimi M.; Steffensen, Isabella; Miguel, Red Thaddeus D.; Babic, Tanja; Johnson, Aubrey D.; Carlone, Julien; Potts, Ryan; Junker, Christopher S. (Frontiers in Cardiovascular Medicine, 2023)
Associations between cigarette smoking and increased risk of cardiovascular disease are well established. However, it is unclear whether the association is mediated by exposure to nicotine and/or to other constituents in cigarette smoke. The objective of this systematic review and meta-analysis of randomized control trials (RCTs) was to identify any potential associations between exposure to nicotine and the risk of clinically diagnosed adverse cardiovascular events in adult current users and nonusers of tobacco products. Among 1,996 results, 42 studies, comparing nicotine and non-nicotine groups, were included and were both qualitatively and quantitatively synthesized across the outcomes of arrhythmia, nonfatal myocardial infarction, nonfatal stroke, and cardiovascular death. The majority of studies evaluating nonfatal myocardial infarction, nonfatal stroke, and cardiovascular death reported no events that occurred in either the nicotine or non-nicotine control groups. Among the studies that reported events, rates of adverse events were similarly low between both groups. Consistent with findings from previous systematic reviews and meta-analyses, pooled data showed that rates for arrhythmia, nonfatal myocardial infarction, nonfatal stroke, and cardiovascular death were not significantly different between nicotine and non-nicotine groups. The overall quality of the body of evidence for each of the four outcomes of interest was graded as “moderate,” limited only by the imprecision of results. The findings of this systematic review and meta-analysis indicate that, with moderate certainty, there are no significant associations between the use of nicotine and the risk of clinically diagnosed adverse cardiovascular events—specifically, arrhythmia, nonfatal myocardial infarction, nonfatal stroke, and cardiovascular death.